2019
DOI: 10.1128/microbiolspec.gpp3-0004-2018
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae: Invasion and Inflammation

Abstract: Streptococcus pneumoniae (the pneumoccus) is the leading cause of otitis media, community-acquired pneumonia, and bacterial meningitis. The success of the pneumococcus stems from its ability to persist in the population as a commensal and avoid killing by immune system. This chapter first reviews the molecular mechanisms that allow the pneumococcus to colonize and spread from one anatomical site to the next. Then, it discusses the mechanisms of inflammation and cytotoxicity during emerging and classical pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 191 publications
(216 reference statements)
3
83
0
3
Order By: Relevance
“…Sp is a bacterium that has traditionally infected the respiratory system [ 21 ], whereas Fn is a bacterium that has mainly occupied the human oral cavity [ 1 , 2 ]. Incubating human respiratory epithelial cells with heat-killed Fn and, subsequently, comparing the results to human respiratory epithelial cells incubated with heat-killed Sp would shed light on the virulence potential of Fn in regard to human respiratory epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Sp is a bacterium that has traditionally infected the respiratory system [ 21 ], whereas Fn is a bacterium that has mainly occupied the human oral cavity [ 1 , 2 ]. Incubating human respiratory epithelial cells with heat-killed Fn and, subsequently, comparing the results to human respiratory epithelial cells incubated with heat-killed Sp would shed light on the virulence potential of Fn in regard to human respiratory epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, S. pneumoniae is increasingly resistant to the most common clinically used drugs such as beta-lactam antibiotics and macrolides (Schulz and Hammerschmidt, 2013;Gladstone et al, 2019;Peyrani et al, 2019). Moreover, it can express a high number of specific virulence factors that raise pathogenicity by complex mechanisms (Bogaert et al, 2004;Kadioglu et al, 2008;Gamez and Hammerschmidt, 2012;Voss et al, 2012;Doran et al, 2016;Loughran et al, 2019;Subramanian et al, 2019). To ensure successful treatments in the future, it is vital to develop new antimicrobial drugs against pneumococci and their resistant strains, which are not based on the composition of the polysaccharide capsule but on other virulence factors like specific proteins, e.g., choline-binding proteins or lipoproteins (Pérez-Dorado et al, 2012;Kohler et al, 2016;Voß et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have found that in ammation reaction participates in the pathogenesis of CAP patients. C-reactive protein (CRP) and many pro-in ammatory cytokines (IL-1β, TNFα and IL-6) were increased in CAP patients [27][28][29]. In ammatory cytokines were positively associated with the severity among CAP patients [30].…”
Section: Discussionmentioning
confidence: 99%